Methylation status of vault RNA 2-1 promoter is a predictor of glycemic response to glucagon-like peptide-1 analog therapy in type 2 diabetes mellitus. Issue 1 (5th March 2021) - Lin, Chia-Hung; Lee, Yun-Shien; Huang, Yu-Yao; Tsai, Chi-Neu
Abstract : Introduction: Therapeutic efficiency of glucagon-like peptide-1 (GLP-1) analog is about 50%–70% in type 2 diabetes mellitus (T2DM). Discovery of potential genetic biomarkers for prediction of treatment efficiency of GLP-1 analog before therapy is still necessary. We assess whether DNA methylation was associated with glycemic response to GLP-1 analog therapy in patients with poorly controlled T2DM. Research design and methods: Genomic DNA was extracted from the peripheral blood of training (n=10) and validation (n=128) groups of patients with T2DM receiving GLP-1 analogs. DNA methylome was analyzed using Infinium Human Methylation EPIC Bead Chip in the training group. The candidate genes were examined using a pyrosequencing platform in the validation group. The association between DNA methylation status and glycemic response to GLP-1 was analyzed in these patients. Results: The most differential methylation region between those with a good (responsive) and poor (unresponsive) glycemic response to GLP-1 analog therapy was located on chromosome 5q31.1 (135415693 to 135416613), the promoter of VTRNA2-1 in the training group. The methylation status of the VTRNA2-1 promoter was examined in the validation group via pyrosequencing reaction, and the hypomethylation of VTRNA2-1 (<40% methylation) was significantly associated with poor glycemic response to GLP-1 treatment (OR 2.757, 95% CI 1.240 to 6.130, p=0.011). Since the VTRNA2-1 promoter region was previously reported maternal imprinting extended to the adjacent centromeric CCCTC-binding factor site that contained an A/C polymorphism (rs2346018), which was associated with methylation density of VTRNA2-1, this A/C polymorphism was also integrated to analyze association with glycemic response to GLP-1 analog therapy. In patients with the A allele of rs2346018 and hypomethylation (<40%) on the VTRNA2-1 promoter, the OR increased to 4.048 (95% CI 1.438 to 11.389, p=0.007). Conclusions: The glycemic response to GLP-1 analog treatment is associated with the methylation status of the VTRNA2-1 promoter and polymorphism of rs2346018.